From policy to practice: A resource-based assessment of access to human rights - Vranić, Bojana; Vranić, Petar; Mitić, Tadija (Ревија за социјална политика/Journal of Social Policy, 2025)
This study focuses on rudimentary disparities in access to human rights in Serbia, concerned with the severe divide between policy frameworks and their locative implementation. The purpose is to apply a resource-based approach to assess how public resources influence access to basic rights. Within a human rights-based approach framework, we identified and explored the presence or absence of resources that enable the realization of the right to work and the right to health. Field surveys and statistical sources served as the principal means of data collection while the investigation was conducted in 69 local communities within the City of Niš, where the indicators were evaluated and normalized by using the comparative scale. In the unbalanced distribution of public resources necessary for the actualization of rights lie the imperatives for travel, kindergartens, schools, health establishments, and pharmacies, with vulnerable groups such as children, women, the elderly, and persons with disabilities suffering most due to the absence of these resources. Without the infrastructure support at community levels or with its little presence, realization of even the most basic human rights is heavily restricted, despite comprehensive legal and policy commitments. The resource-based approach can serve as a feasible measure to pinpoint local disparities in access to human rights.